How are the students' feelings in the face of school complaints? - Silva, Carolina Santa Rosa da; Lessa, Patrícia Vaz de (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 38 No 75 (2022): jul./dez., 2022)
The school, after the family context, is the environment in which the child spends most of the time, where social relationships are established and the schooling process is constituted, a process that marks a fundamental stage for the child's psychic development. Faced with schooling, learning difficulties may arise, and later be demonstrated by the child through his emotional and/or behavioral reactions. Thus, the research aims to understand what are the feelings that plague the condition of not learning, besides identifying how children with school difficulties deal with their emotions and feelings related to complaints, and also the importance of the school psychologist.The text brings some initial considerations and theoretical basis about the theme, as well as reflections on the work developed in the year of 2021 in a Municipal School in the city of Londrina/PR and in a State School also located in Londrina/PR. In this sense, we understand that the process of building knowledge and feelings is understood in the interconnection of several aspects, such as: school, family, society, economy, culture, among others.